Charles S. Peirce on norms & ideals - Potter, Vincent G. (American philosophy series, 2019)
In Charles S. Peirce: On Norms and Ideals, Potter argues that Peirce's doctrine of the normative sciences is essential to his pragmatism. No part of Peirce's philosophy is bolder than his attempt to establish esthetics, ethics, and logic as the three normative sciences and to argue for the priority of esthetics among the trio. Logic, Potter cites, is normative because it governs thought and aims at truth; ethics is normative because it analyzes the ends to which thought should be directed; esthetics is normative and fundamental because it considers what it means to be an end or something good in itself. This study shows that Peirce took seriously the trinity of normative sciences and demonstrates that these categories apply both to the conduct of man and to the workings of the cosmos.